ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING BISNIS KULINER (STUDI KASUS IKAN BAKAR PAK TIAR KOTA LANGSA) - Dewi Rosa Indah; Zenitha Maulida (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze marketing strategies in improving the competitiveness of culinary businesses at Ikan Bakar Pak Tiar Restaurant in Langsa City. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The analysis of marketing strategies in this study uses the STP approach (Segmenting, Targeting, Positioning) and the 7P service marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence). The results of the study indicate that Ikan Bakar Pak Tiar Restaurant has implemented marketing strategies quite effectively. In terms of the STP strategy, the business conducts market segmentation based on geographic, demographic, and consumer behavior aspects, targets the general public and seafood culinary enthusiasts, and builds a positioning as a grilled fish restaurant with the distinctive culinary taste of Idi Rayeuk and affordable prices. Meanwhile, based on the analysis of the 7P marketing mix, product quality, appropriate pricing, strategic location, promotion through social media and word of mouth, friendly service, fast service processes, and comfortable facilities are the main factors in attracting and retaining customers.